Mobilizing Rural Support: Targeted Government Spending and Democratic Backsliding in Hungary - Krisztina Szabó; Ádám Reiff (Politics and Governance, 2025)
The spread of democratic backsliding has drawn scholarly attention to the strategies and approaches characteristic of these regimes. However, our understanding of targeted government spending programs designed to favor specific segments of society to build and reinforce a loyal support base remains largely limited. We explore a major targeted government spending initiative directed at rural settlements in Hungary, one of the most notable cases of democratic backsliding today. In particular, we analyze the electoral and mobilization effects of targeted policies and the government’s resource allocation strategy, focusing on two initiatives: the Rural Family Housing Allowance Program (Rural CSOK), which provides housing subsidies to individuals in eligible settlements, and the Hungarian Village Program, which funds local governments in eligible settlements to invest in essential infrastructure, public services, and community spaces. Using highly detailed observational data and leveraging the quasi-random assignment of program eligibility, we show that the government directs Hungarian Village Program funds to reward electorally strong core settlements. We also find that both eligibility and subsidy amounts increase government vote share by mobilizing core and inactive voters while discouraging opposition participation.